Thermodynamic modelling of a novel solar-ORC with bottoming ammonia-water absorption cycle (SORCAS) powered by a vapour compression refrigeration condensate for combined cooling and power - Fidelis Ibiang Abam; Macmanus Chinenye Ndukwu; Oliver Ibor Inah; Onyishi Donatus Uchechukwu; Muji Setiyo; Olusegun David Samuel; Remy Uche (Mechanical Engineering for Society and Industry, 2023)
The current study proposed an innovative combined power and cooling solar Organic Rankine Cycle (ORC) with bottoming vapour absorption (VAS) and vapour compression refrigeration (VCP) cycles using ammonia–water as the working fluid. The advantage of these cycles is the integration of two cooling evaporators, producing equivalent refrigerating effects from the VCP condensate. The power generation sub-system, the topping cycle, employed a solar-driven ORC. At operating conditions, the energy and exergy efficiencies stood at 38.63 and 42.09%, respectively, with overall refrigerating effect, power output, and COP calculated at 1358 kW, 26.65 kW, and 2.34 in that order. The parametric results indicated a 40% and 55% increase in energy and exergy efficiencies at high turbine inlet temperatures, with a 1.73 % increase in refrigerating effect and a 1.56% decrease in the exergy of cooling. Similarly, at an elevated generator pressure of 4.75 bar, an overall COP of 3.046 was reached. The total exergy of products and fuel was calculated at 1347.91 and 786.38 kW, respectively, with an exergy destruction ratio of 0.997. The results showed a total improvement potential (IP) of 426.768 kW, with the evaporators, absorber, and heat exchanger having the highest IP of 66. 32, 119.4, and 68.08 kW respectively. The study showed enhancement in performance when compared with previous studies and recommended system optimization and sustainability analysis as future considerations for system practical application.